Antibodies targeting Clec9A promote strong humoral immunity without adjuvant in mice and non‐human primates. Issue 3 (14th January 2015) - Li, Jessica; Ahmet, Fatma; Sullivan, Lucy C.; Brooks, Andrew G.; Kent, Stephen J.; De Rose, Robert; Salazar, Andres M.; Reis e Sousa, Caetano; Shortman, Ken; Lahoud, Mireille H.; Heath, William R.; Caminschi, Irina
<x xml:space="preserve">Abstract</x> Targeting antigens to dendritic cell (DC) surface receptors using antibodies has been successfully used to generate strong immune responses and is currently in clinical trials for cancer immunotherapy. Whilst cancer immunotherapy focuses on the induction of CD8+ T‐cell responses, many successful vaccines to pathogens or their toxins utilize humoral immunity as the primary effector mechanism. Universally, these approaches have used adjuvants or pathogen material that augment humoral responses. However, adjuvants are associated with safety issues. One approach, successfully used in the mouse, to generate strong humoral responses in the absence of adjuvant is to target antigen to Clec9A, also known as DNGR‐1, a receptor on CD8α+ DCs. Here, we address two issues relating to clinical application. First, we address the issue of variable adjuvant‐dependence for different antibodies targeting mouse Clec9A. We show that multiple sites on Clec9A can be successfully targeted, but that strong in vivo binding and provision of suitable helper T cell determinants was essential for efficacy. Second, we show that induction of humoral immunity to CLEC9A‐targeted antigens is extremely effective in nonhuman primates, in an adjuvant‐free setting. Our findings support extending this vaccination approach to humans and offer important insights into targeting design.